Analysis of Factors Influencing Open Defecation Behavior in Coastal Areas of Indonesia: A Review - Listy Handayani; Rini; Inochi Lara Palino (Journal of Health Science and Pharmacy, 2025)
Background: Open defecation free (ODF) status is essential for protecting both environmental quality and public health. Open defecation, which refers to the practice of defecating in open spaces such as rice fields, forests, rivers, beaches, or the sea, can inadvertently contaminate water sources and soil, posing serious health risks. In Indonesia, access to improved sanitation has shown progressive improvement, with the national open defecation rate decreasing from 7.61% in 2019 to 6.19% in 2020, and further declining to 5.69% in 2021. Despite this progress, open defecation remains a persistent issue, particularly in coastal regions. Objective: This study aims to explore the factors associated with open defecation behavior in coastal areas of Indonesia. Methods: A qualitative literature review method was employed to synthesize findings from relevant studies. National publications were retrieved using the Google Scholar database with the keyword "Coastal ODF" for the period 2017–2025. A total of 267 journals were initially identified, and after screening for title relevance and thematic alignment, 20 journals were selected for in-depth analysis. The selected literature was then compared and thematically analyzed to identify key influencing factors. Results: The review identified several contributing factors to open defecation behavior in coastal communities. These factors were categorized into three domains: (1) Predisposing factors, including age, income, education level, knowledge, attitudes, and perceived health risks; (2) Enabling factors, such as latrine ownership, availability of clean water, geographical constraints, and the distance to sanitation facilities; and (3) Reinforcing factors, which encompass the involvement of health workers, family leadership roles, and social support networks. Conclusion: To ensure environmental sustainability and protect public health, communities must be encouraged to eliminate open defecation practices. Such behavior not only contributes to environmental degradation but also facilitates the spread of disease vectors, creates unpleasant odors, and diminishes the aesthetic quality of public spaces. Addressing this issue aligns with the pillars of the Community-Based Total Sanitation program. Active collaboration among village authorities, community leaders, religious figures, and health professionals is essential to promote healthy sanitation behaviors and foster a culture of hygiene in coastal communities. Keywords: Public Health, Sanitation, Open Defecation, Indonesia.